Estudo sobre a racionalização na construção civil - Vaz, Priscila Fernandes Lage (2014)
The Construction industry in Brazil is growing rapidly and there is great concern among entrepreneurs to your stabilizing in highly competitive market, the rationalization of the construction is a tool that enables professionals the processes upgrading related to civilian production, with measures that enhance the features offered and others able to minimize the incalculable losses generated by the non use of rationality, in most cases unnecessary and correctable, with a rational and careful insight into the production process it is possible to obtain good results proved by case studies, with the improvement of the steps involved in the building, and from the analysis of the feasibility, through design and implementation, to final product delivery. In this context, this is the importance of discussing about rationalization of construction and with the help of several bibliographies of numerous distinct authors, the work has as main objective the theoretical research on the subject, mainly discussion on the production management at construction, emphasizing its importance and offering the necessary material to correct possible faults and consequently loss in many wherewithal human, material, financial and time dedicated to the production of buildings.